Bioprospection of cold-adapted yeasts with biotechnological potential from Antarctica - Martorell, María Martha; Ruberto, Lucas Adolfo Mauro; Fernandez, Pablo Marcelo; Castellanos, Lucia Ines; Mac Cormack, Walter Patricio (Journal of Basic Microbiology)
The aim of this study was to investigate the ability to produce extracellular hydrolytic enzymes at low temperature of yeasts isolated from 25 de Mayo island, Antarctica, and to identify those exhibiting one or more of the evaluated enzymatic activities. A total of 105 yeast isolates were obtained from different samples and 66 were identified. They belonged to 12 basidiomycetous and four ascomycetous genera. Most of the isolates were ascribed to the genera Cryptococcus, Mrakia, Cystobasidium, Rhodotorula, Gueomyces, Phenoliferia, Leucosporidium, and Pichia. Results from enzymes production at low temperatures revealed that the Antarctic environment contains metabolically diverse cultivable yeasts, which represent potential tools for biotechnological applications. While most the isolates proved to produce 2-4 of the investigated exoenzymes, two of them evidenced the six evaluated enzymatic activities: Pichia caribbica and Guehomyces pullulans, which were characterized as psycrotolerant and psycrophilic, respectively. In addition, P. caribbica could assimilate several n-alkanes and diesel fuel. The enzyme production profile and hydrocarbons assimilation capacity, combined with its high level of biomass production and the extended exponential growth phase make P. caribbica a promising tool for cold environments biotechnological purposes in the field of cold-enzymes production and oil spills bioremediation as well. Fil: Martorell, María Martha. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y ...